PT Seabank Indonesia’s Financial Performance: Pre- and Post-Digital Banking Acquisition - Jessyca; Munaf, Tommy; Sambodo, Bambang; Saputra, Novi Chandra; Zulaika, Nurfitri (Indonesian Scientific Publication, 2025)
This research investigates the financial performance of PT Seabank Indonesia prior to and following its acquisition and transformation into a digital bank. The evaluation is based on several key financial indicators, including the Loan to Deposit Ratio, Capital Adequacy Ratio, Return on Assets, and the ratio of Operating Expenses to Operating Income. Using a quantitative method, this research analyzes secondary data drawn from quarterly financial reports between 2019 and 2022. Statistical tests, including the Paired Sample T-Test and Wilcoxon Signed Rank Test using SPSS version 29, were employed to assess differences before and after the acquisition. The findings reveal that only the LDR ratio showed a significant change post-acquisition, while CAR, ROA, and BOPO did not exhibit statistically significant differences. These results suggest that while digital transformation may influence certain aspects of bank performance, its overall financial impact may vary across different indicators.